Erwiniaceae bacteria play defensive and nutritional roles in two widespread ambrosia beetles - Cambronero Heinrichs, Juan Carlos (2023)
Ambrosia beetles are fungal-growing insects excavating galleries deep inside the wood. Their success as invaders increased scientific interest towards them. However, most studies on their microbiota targeted their fungal associates whereas the role of bacterial associates is understudied. To explore the role of abundant microbial associates, we isolated bacteria from active galleries of two widespread ambrosia beetles, Xylosandrus crassiusculus and X. germanus. These isolates were classified within the Erwiniaceae family and through a phylogenetic analysis including isolates from other insects we showed that they clustered with isolates obtained from ambrosia and bark beetles, including Erwinia typographi. The whole genome analysis of the isolate from active galleries of X. crassiusculus suggested that this bacterium plays both a nutritional role, by providing essential amino acids and enzymes for the hydrolysis of plant biomass, and a defensive role, by producing antibiotics. This defensive role was also tested in vitro against fungi, including mutualists, common associates, and parasites. The bacteria inhibited the growth of some of the common associates and parasites but did not affect mutualists. Our study supported the hypothesis of a mutualist role of Erwiniaceae bacteria in ambrosia beetles and highlighed the importance of bacteria in maintaining the symbiosis of their host with nutritional fungi.